Eindexamen 1996. : Academie van Beeldende Kunsten Rotterdam. - Berkulin, Arie; Koonijnendijk, Burgert; van Gemert, Anton (Rotterdam : Academie van Beeldende Kunsten, 1996)
Blonk, Jeanette ; de Bruijn, Frank ; Greijn, Marjan ; Groenewegen, Conny ; Hak, Belinda ; Kooijmans, Renate ; Limburg, Geert-Jan ; Maaskant, Mariëtte ; Mercx, Norbert ; Rademeijer, Sonya ; Stavenuiter, Chaim ; Stuurman, Otto Jasper ; de Walle, Juliette van ; Weemering, Hans Christiaan ; Witteveen, Barbara ; Alves, Paulo ; de Bloeme, Ronald ; Blom, Minke ; Castel, Ellis ; Clausen, Hanne ; Daglish, Alexander ; van Dam, Hannah ; Aray, Maria Davelos ; van Drongelen, Remko ; Alpaytac, Hüma Gruaz ; Hollaar, Wolf ; Klapwijk, Marianne E. ; de Lange, Freddy ; Mooren, Marije ; Mouyal, Lorien ; Palermo, Cecilia ; Patijn, Emilie ; van der Pols, Sarah ; Schuitemaker, Ina ; van Toor, Anne ; Versluis, Celinda ; Visser, Erik ; van der Vlugt, Ingrid ; van Vollenhoven, Ellen ; Went, Floriaan ; Zuidmeer, Mischa ; Zwijnenburg, Carolien ; Groen, Ries ; de Jong, Rob ; van der Kaaij, Thijs ; Kester, Lieke ; Samson, Daan ; Boer, Johan ; Dekkers, Marloes ; Durinck, Corné ; Geenevasen, Marcel ; de Hoogh, Mira ; Huige, Anouska ; van Maurik, Simone C.C. ; Neefjes, Johan ; Raaphorst, Richard ; Reinds, Denn ; Roelofs, Elly ; Boersma, Anna Wikje Roorde ; Rosenau, Robert ; Spel, Marcella ; van den Tillaar, Nathalie ; Uiterwijk, Michel ; Baars, Frederieke ; van Beest, Mark ; Blokland, Marie-José ; Boelens, Ariënne ; Bolderheij, Lonneke ; Brouwer, Saskia ; de Bruijn, Maurits ; de Bruijn, Pauline ; de Bruin, Barry ; Cornelissen, Micha ; Couwenbergh, Caroline ; Groenewegen, Eelko ; Handke, Moniek ; Hove, Misjka ten ; Hvalsbrâten, Harald Anders ; Inklaar, Fred ; van Leeuwen, Esther ; van Leuven, Martijn ; Lute, Cees ; Lumatalate, Nicky ; Mooren, Maureen ; Noordam, Wim ; Perrin, Zoé ; Lopez, A. Rodriguez ; Scheele, J. ; Scholi, Ellen ; Schoonenburg, Peter M. ; Schriever, Sven ; etc.
Eindexamen 1996, Academie van Beeldende Kunsten, Rotterdam, 1996
Nederlands
kunstcatalogus